Geoelectric Evaluation of Groundwater Potential: A Case Study of Sabongida-Ora and Environs, Southern Nigeria - FI Chinyem (Journal of Applied Sciences and Environmental Management, 2013)
A d.c resistivity investigation for groundwater was carried out in Sabongida-Ora and its environs of Owan West Local Government of Edo State. A total of seven vertical electrical sounding (VES) was carried out using the Schlumberger configuration with a maximum current electrode spacing ranging from 500- 650m. The data was interpreted using conventional partial curve matching and computer aided iteration techniques. Seven hybrid curve types were deduced viz: KHAHQH, KHKHA, KHAKQQ, QQHKH, HKHAA, QHKHA, and KQHKQ. The results showed seven to eight geoeletrical layers with resistivity values ranging from 127Ωm to 767Ωm, 47Ωm to 672Ωm, 70Ωm to 1380Ωm, 4Ωm to 428Ωm and 21Ωm to 400Ωm for the first to eight layers respectively with lithologies consisting of clay, clayey sand and coarse grained sand as indicating in the computed model parameters and geoeletrical section. From the geoelectric section, the area shows a vertical and lateral lithologic heterogeneity as a result of variation in depositional conditions which made unit correlation between the VES stations difficult. Nevertheless, borehole lithologic logs were also correlated with the geoelectric section and similar lithologies were observed. The section showed the occurrence of confined aquifer at a depth range of 60-100m in some places and variable in other places. Results from both data revealed clay layers to be dominant in the study. It is therefore paramount to carry out a thorough geophysical investigation in any locality prior to sinking a borehole in order to forestall loses and to have productive wells. @JASEM